Voting in the European Union - Central Europe's lost voice - Ondřej Schneider (Charles University in Prague, Institute of Economic Studies (IES), 2008)
Ten Central European countries became members of the European Union in the years 2004 - 2007. They constitute 20% of the EU's total population; and even though their economic output is much lower, it rises dynamically. New members' impact on the EU policies has nevertheless been limited. This is due not only to the arcane voting rules within the EU, but also to the lack of a common agenda among the Central European countries. Our paper illustrates that the new members rarely vote together and that their influence is thus fairly limited. We argue that as the EU seemingly lacks energy to implement further reforms that would stimulate its economy, impetus for change may come from Central European countries. To that end, however, they have to coordinate their voting and become a more coherent voting group than they are now.
Keywords: J08; J51; K31; 330; European Union; voting system; European Council; new member states; EU-Politik; Abstimmungsregel; Abstimmung; EU-Staaten (Osteuropa); EU-Staaten